Implementasi Sistem Pengendalian Manajemen pada UMKM Batik Lasem - Veronica Puspitasari; Dyna Rachmawati; Crescentia Shelfina (STIE Indonesia Banking School, 2018)
The competition between the newly established batik business and a business that has been handed down in Lasem Subdistrict has made an owner must have a management control system in his business which is useful for achieving the stated goals. This study will discuss the implementation of management control systems in Batik Lasem MSMEs with the aim of analyze strategic planning, budgeting, and performance measures in Griya Batik Gajah and Indah Aneka Warna, while also discussing comparisons between the two MSMEs. This research is descriptive research with the object of research in the Batik Lasem UMKM which has changed ownership for four years and eight years, namely Griya Batik Gajah and Indah Aneka Warna. The source of the data is taken from the results of interviews and observations with the owners of the batik businesses. The results showed that the stages in strategic planning, in Griya Batik Gajah and Indah Aneka Warna have not performed optimally because owners argued that batik business still belongs to small business. Phases in the preparation of the budget has not yet been performed in its entirety, the owner just do simple budget drafting. Performance measures also has not performed in its entirety, both companies did not do an evaluation in terms of employee retention because that employees enter by com-paring salary obtained is reasonable in the batik business, as well as the evaluation of the reduction time cycle is not done because the number of employees is in accordance with the existing work .